Anticancer and Antimicrobial Studies on Mannich Bases of β-Diketones - Siddiqui, A.A.; Rajesh, R.; Ramasarma, G.V.S. (Asian Journal of Chemistry, 2010)
Anticancer and antimicrobial activities of some 2-(N-aryl/heteroarylaminomethyl)-1,3-diphenyl/1-phenyl-3-(3-nitrophenyl)/1-phenyl-3-(pyridin-3-yl) propan-1,3-diones were determined by adopting standard methods. Among the compounds tested the compounds IX and VI excel in their anticancer activity. In antibacterial screening, the same compounds showed more appreciable activity than the standard. In antifungal screening, all the compounds showed activity at 100 μ/mL.